EKONOMI ISLAM SEBAGAI PILAR PERADABAN: MENJAJAKI SOLUSI TANTANGAN EKONOMI GLOBAL MODERN - Rupita, Nanda Ega; Azzaki, Adnan (Fakultas Ekonomi dan Bisnis Islam Institut Pesantren Sunan Drajat Lamongan, 2025)
Islamic economics has played a crucial role in supporting classical Islamic civilization, particularly during the Abbasid Caliphate and Andalusia. Based on principles of justice, equality, and sustainability, Islamic economics integrates material and spiritual aspects in economic management. Instruments such as zakat, waqf, and the prohibition of riba have proven effective in promoting fair wealth redistribution, social stability, and sustainable development.This study aims to examine the relevance of Islamic economic principles in addressing modern global economic challenges, such as social inequality, financial crises, and environmental degradation. Using a literature review with a descriptive approach, this study analyzes how zakat, waqf, and the prohibition of riba can provide solutions to these issues. The findings show that zakat and waqf play a significant role in reducing social inequality and supporting sustainable development, while the prohibition of riba helps ensure economic stability by avoiding speculation. The study concludes that the application of Islamic economic principles can provide solutions for building a more just and sustainable civilization in the modern era.